Relevansi Selera Musikal dengan Politik Golongan di Indonesia Era Soekarno - Ali, Arhamuddin (PANTUN, 2016)
The aim of this study is to explain differences in musical tastes in upper social class. The study alsodescribes the relationship between musical tastes with the political groups in the community of Indonesia in Sukarno era. As a conceptual basis, we use the views of Bourdieu about habitus, arenas, andcultural capital. Also used a conceptual view of the Schuessler relationship of musical tastes and ages.This case study concludes that the old group closed with the development of new music tends to assumethe old music as the best. On the other side, the young man open to the development of new types ofmusic. Besides, the differences in musical tastes of young and old groups lead to a clash between them.Differences in their taste of music creates an identity as a differentiator between them, resulting in aprocess of political groups in it.Keywords: musical tastes, political group, age and identity